URGENSI PENDIDIKAN KEWARGANEGARAAN DALAM MEMBENTUK KARAKTER GENERASI MUDA DI INDONESIA - man, Herman man (Makassar Journal of Social Sciences, 2013)
The character is an integral part that should be built, so that the younger generation has an attitude and mindset that is based on Pancasila and the 1945 Constitution through civic education or civil  education, character development of the nation as the next generation[1] has to start from the individual's own character development, strengthening the construction of the spiritual, and moral an important priority in order to become strong moral beings